2021
DOI: 10.1139/cjfr-2019-0438
|View full text |Cite
|
Sign up to set email alerts
|

Initial productivity and genetic parameters of three Corymbia species in Brazil: designing a breeding strategy

Abstract: The survival, initial productivity and the genetic parameters of <i>C. citriodora</i> subsp. <i>citriodora</i> (CCC), <i>C. citriodora</i> subsp. <i>variegata</i> (CCV) and <i>C. torelliana</i> (CT) were used to develop a breeding strategy for the <i>Corymbia</i> species. Survival, height and diameter at breast height (DBH) data were assessed 24 and 36 months after planting and the mean annual volume increment estimated in three trials. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 170 publications
(244 reference statements)
1
5
0
Order By: Relevance
“…The three species exhibited high survival, above 95% (Table 2), indicating high adaptation, without significant differences for survival regarding seedlots/provenances. Similar studies have reported comparable survival values for CH (93%) in the region (Silva et al 2017), as well as CCV (93%) and CT (95%) in the same location (Araujo et al 2021). However, it is noteworthy that CCV survival rates under different Brazilian climatic conditions vary widely from 50 to 96% three years after planting (Silva et al 2017).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The three species exhibited high survival, above 95% (Table 2), indicating high adaptation, without significant differences for survival regarding seedlots/provenances. Similar studies have reported comparable survival values for CH (93%) in the region (Silva et al 2017), as well as CCV (93%) and CT (95%) in the same location (Araujo et al 2021). However, it is noteworthy that CCV survival rates under different Brazilian climatic conditions vary widely from 50 to 96% three years after planting (Silva et al 2017).…”
Section: Resultssupporting
confidence: 75%
“…Species of the genus Corymbia have growth potential under several Brazilian climatic conditions. However, their potential has only been explored recently (Silva et al 2017, Tambarussi et al 2018, Araujo et al 2021. Diversification of species and genera for commercial planting is a way to reduce plantation vulnerability to biotic and abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the origin/provenance has a strong influence on the genotype performance, tolerance to biotic and abiotic stresses, and wood quality. The effect of provenance has been observed and reported for several species in different countries, such as in Corymbia citriodora sub variegata (Araujo et al 2021;Silva et al 2022), Eucalyptus grandis (Ferreira 2015;Silva, Marco, et al 2019), E. pellita (Nieto et al 2016), E. pilularis (Carnegie, Johnson & Henson 2004), including E. urophylla itself (Hodge & Dvorak 2015).…”
Section: Introductionmentioning
confidence: 96%
“…The narrow-sense heritability between progenies ( ℎ "# $ ) values for DBH in half-sibling progenies of Corymbia was lower than the ones reported by Araujo et al (2020), which varied from 0.41 to 0.69. According to Lima et al (2019), the traditional mixed model methodology commonly overestimate genetic parameters estimates and consequently narrowsense heritability for growth traits in comparison to methodologies that consider the genomic relationship matrix.…”
Section: Genetic Parametersmentioning
confidence: 65%